2022
DOI: 10.3390/foods11223691
|View full text |Cite
|
Sign up to set email alerts
|

Quality Attributes of Sesame Butter (Tahini) Fortified with Lyophilized Powder of Edible Mushroom (Agaricus blazei)

Abstract: Sesame butter (tahini) is a common appetizer and food additive in the Mediterranean basin. Pathogenic strains and mycotoxin content are the most hazardous issues in the final product. This investigation aimed to enhance the quality and safety properties of tahini products against microbial hazards and mycotoxins. Local samples of tahini were evaluated for natural contamination, including mycotoxin level determinations. Agaricus blazei was utilized as a bioactive source and evaluated for the bioactive content o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 51 publications
0
3
1
Order By: Relevance
“…In another study by Alvarez et al[19], they found that the values of the colors L * , a * , and b * in hummus were 75.3, 0.29, and 14.3, respectively. The difference between the results of those studies and our results may be attributed to the color of each legume used, which contains several pigments at different levels, including carotenoids, chlorophyll, and flavonoids, as well as to tahini, whose values of L * , a * , and b * are 55.37, 5.61, and 12.23, respectively[51].…”
contrasting
confidence: 97%
“…In another study by Alvarez et al[19], they found that the values of the colors L * , a * , and b * in hummus were 75.3, 0.29, and 14.3, respectively. The difference between the results of those studies and our results may be attributed to the color of each legume used, which contains several pigments at different levels, including carotenoids, chlorophyll, and flavonoids, as well as to tahini, whose values of L * , a * , and b * are 55.37, 5.61, and 12.23, respectively[51].…”
contrasting
confidence: 97%
“…Flasks were classified for treatment by chitosan nanoemulsion loaded with 0, 50, 100, 150, and 200 ng propolis extract and the control (free of nanoemulsion treatment). The degradation of the mycelia growth of Fusarium fungi and the ability for zearalenone reduction was determined by the same methodology using the VICAM instrument (VICAM Series 4EX Fluorometer) as reported before [43].…”
Section: Assessment Of the Anti-mycotoxigenic Activitymentioning
confidence: 99%
“…Several applications were recorded by efficiently reducing the aflatoxin contamination using antagonism impact [ 14 ]. Otherwise, the application of natural extracts rich in bioactive molecules can reduce these types of hazards [ 15 , 16 ]. In addition to antifungal potentials, the Lactobacillus bacterial strain showed many anti-mycotoxigenic possibilities to be widely used in food and feed commodities to either inhibit the production of mycotoxins or reduce the quantity of already produced mycotoxins through physical and chemical binding involving the use of acidification and absorbents with a multi-mycotoxin binding capacity [ 17 ].…”
Section: Introductionmentioning
confidence: 99%